2019
DOI: 10.1161/jaha.118.011825
|View full text |Cite
|
Sign up to set email alerts
|

Association of Concurrent Changes in Metabolic Health and Weight on Cardiovascular Disease Risk: A Nationally Representative Cohort Study

Abstract: BackgroundThe combined effect of transitions of metabolic health and weight on cardiovascular disease (CVD) remains unclear. We aimed to examine the association of concurrent changes of metabolic health and weight on CVD over time.Methods and ResultsThe study population consisted of 205 394 from the Korean National Health Insurance Service. Metabolic health was determined by fasting serum glucose, total cholesterol, and blood pressure levels, while obesity was determined by body mass index. All participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
2
16
0
1
Order By: Relevance
“…The NHIS-HEALS provides cohort data of participants who undergo health screening examinations for research purposes 44 . It has been used in several epidemiological studies, and its validity is described in detail elsewhere 45 , 46 .…”
Section: Methodsmentioning
confidence: 99%
“…The NHIS-HEALS provides cohort data of participants who undergo health screening examinations for research purposes 44 . It has been used in several epidemiological studies, and its validity is described in detail elsewhere 45 , 46 .…”
Section: Methodsmentioning
confidence: 99%
“…In adults, poor metabolic health status has been associated with greater adverse changes in cardiac structure and function than obesity alone 48 and prospective changes toward metabolically unhealthy or obese states resulted in increased CVD risk. 49 Previous findings in adolescents showed that poor metabolic health was related to an unfavourable inflammatory status and endothelial dysfunction. 23 In addition, it has been observed among European adolescents that metabolic health is associated with high concentrations of hsCRP.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous studies, this work offers a more comprehensive picture that simultaneously describes the complex interrelationships between metabolic healthy or unhealthy phenotypes and 10-year CVD risk across BMI categories, as well as the relationships among CVD-related risk factors. Although several prospective cohort studies have focused on exploring the specific associations between CVD risk and metabolic health status and BMI categories [14,[45][46][47], or the dynamic risk in the transition from one phenotype to another [48][49][50], this work aimed to provide a general framework to understand the multiple association processes that can emerge from the complex interrelationships between these factors. In fact, compared with standard studies, the greatest advantage and strength of this BN methodological approach is the graphical clarification and visualization of the most probable pathways in these relationships from a multi-dependent perspective, without affecting the interpretability of the network.…”
Section: Principal Findingsmentioning
confidence: 99%